PENGARUH KOMUNIKASI DAN PENGEMBANGAN KARIR TERHADAP PRESTASI KERJA KARYAWAN DI PT. ALFAMART WILAYAH PAMULANG, TANGERANG SELATAN - Sindi Anita Debi; Yusran Daeng Matta (Journal of Research and Publication Innovation, 2024)
This study aims to determine the extent to which communication and career development influence employee performance at PT. Alfamart, Pamulang Region, South Tangerang, both partially, and simultaneously. The method used is quantitative, with data collection techniques including field research such as observation, and questionnaires, literature study, and data analysis. The population in this study consists of all employees at PT. Alfamart, Pamulang Region, South Tangerang, totaling 129 people. Using a saturated sampling technique, the sample size for this study is 129 respondents. The results of this study are: 1) There is an influence of communication on employee performance at PT. Alfamart, Pamulang Region, South Tangerang. This is evidenced by the partial t-test results showing that the t-value > t-table (19.919 > 1.978), and significance is less than 5% (0.000 < 0.050), reinforced by a Determination Coefficient value contributing 75.8%. 2) There is an influence of career development on employee performance at PT. Alfamart, Pamulang Region, South Tangerang. This is evidenced by the partial t-test results showing that the t-value > t-table (13.415 > 1.978), and significance is less than 5% (0.000 < 0.050), reinforced by a Determination Coefficient value contributing 58.6%. 3) There is an influence of communication and career development on employee performance at PT. Alfamart, Pamulang Region, South Tangerang. This is evidenced by the simultaneous F-test results showing that the F-value > F-table (206.273 > 2.68), with a significance level of (0.000 < 0.050), reinforced by a Determination Coefficient value contributing 76.6%. To improve employee performance, the company is advised to enhance internal communication by providing communication skills training, and assessing the physical conditions of the workplace. Additionally, the company should develop a clearer and more structured career plan and consider a mentorship program to guide less experienced employees.